Student Interactive Study Guide on CD-ROM - Mc Shane (Mc Graw Hill, 2005)
Besar file 59 MB, Berisi : McShane (Build Your Management Skills, Chapter Summaries, Flashcards, OBOnline, Online Learning Center, Quizzes, Self Assessment Exercises), Support, dan Xtras.